Audit committee, real earnings management, and firm value: Evidence from Indonesia - Arya Pradipta; Magda Siahaan (AFRE (Accounting and Financial Review), 2026)
This study investigates how audit committee effectiveness and real earnings management influence firm value by examining the mediating role of profitability and the moderating role of the debt-to-equity ratio (DER). Although prior studies have documented the direct effects of corporate governance and earnings management on firm value, limited evidence explains the underlying mechanism through which these relationships operate under different capital structure conditions. Using secondary data from 330 firm-year observations of Indonesian manufacturing companies during 2022–2024, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM), which is appropriate for simultaneously estimating multiple direct, mediating, and moderating relationships within a complex structural model. The results indicate that the audit committee improves firm value indirectly through profitability, whereas real earnings management negatively affects firm value. Furthermore, DER moderates these relationships, indicating that leverage alters the effectiveness of governance and profitability in enhancing firm value. Theoretically, this study extends Contingency Theory by demonstrating that capital structure conditions shape governance effectiveness. Methodologically, it illustrates the usefulness of PLS-SEM for simultaneously evaluating mediation and moderation effects in corporate governance research. From an accounting perspective, the findings provide evidence that governance quality, earnings management, and capital structure jointly influence firm value through financial performance.